Biochar derived from fruit by-products using pyrolysis process for the elimination of Pb(II) ion: An updated review - Farihahusnah, H. *; Aroua, M. Kheireddine *; Szlachta, M. (Elsevier, 2022)
Water pollution is one of the most concerning global environmental problems in this century with the severity and complexity of the issue increases every day. One of the major contributors to water pollution is the discharge of harmful heavy metal wastes into the rivers and water bodies. Without proper treatment, the release of these harmful inorganic waste would endanger the environment by contaminating the food chains of living organisms, hence, leading to potential health risks to humans. The adsorption method has become one of the cost-effective alternative treatments to eliminate heavy metal ions. Since the type of adsorbent material is the most vital factor that determines the effectiveness of the adsorption, continuous efforts have been made in search of cheap adsorbents derived from a variety of waste materials. Fruit waste can be transformed into valuable products, such as biochar, as they are composed of many functional groups, including carboxylic groups and lignin, which is effective in metal binding. The main objective of this study was to review the potential of various types of fruit wastes as an alternative adsorbent for Pb(II) removal. Following a brief overview of the properties and effects of Pb(II), this study discussed the equilibrium isotherms and adsorption kinetic by various adsorption models. The possible adsorption mechanisms and regeneration study for Pb(II) removal were also elaborated in detail to provide a clear understanding of biochar produced using the pyrolysis technique. The future prospects of fruit waste as an adsorbent for the removal of Pb(II) was also highlighted.